Development of e-Module in Learning Ecosystem to Foster Thinking Skills of Junior High School Students - Lalusu, Sri Lesnawati; Latjompoh, Masra; Baderan, Dewi Wahyuni Kyai (FKIP Universitas Lampung, 2022)
The aim of this study is to develop a flipped-classroom-based e-module through validity, practicality, and effectiveness test. The method employed in this study is research and development (R&D) with several steps undergone i.e. planning, product development, validity test, revision, and small- and big-scales try-out. The result of this study revealed that the e module had been very valid based on the input given by the content and media experts with approximate score 91.76% to 98.40%. The practicality on teacher’s and students’ activity for the whole meeting reached the approximate score 84.44% to 98.10% which is very practical. Students’ response on the response on the questionnaire reached the highest score as big as 94.07% which was very good. On the effectiveness test, there was an increase on students’ solo taxonomy level. It can be seen from the pre-test which was initially on the pre-structural (59.17%) and uni-structural (40.83%) level elevated to the multi-structural (85%) and relational (12.50%) level during the post-test. The evaluation on the mockup product, the range score on each group is around 83.53 to 90.59 which is very good. It can be concluded that the flipped classroom based e-module had fulfilled the criteria of validity, practicality, and effectiveness to foster students’ thinking skill in SMP Islam Pagimana. Keywords: e-modul, flipped classroom, ecosystem, thinking skills. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp606-623